Detection of deoxynivalenol (DON) using europium chelates and magnetic nanoparticles - Bin Zhou; Xueyu Yuan; Yonghong Hu; Jun Fan; Wenge Yang; Mingming Guo; Yi Zhang; Wenxin Li; Jue Zhang (Food and Agricultural Immunology, 2019)
Background: Several immunoassay methods have been developed for the detection of DON in cereal. However, there has been no method based on Eu-chelate antibody-conjugated magnetic nanoparticles established. Methods: Indirect competition for DON detection was established by combining Eu-chelate and immunomagnetic separation. The immunocomplex was separated and washed by exposure to a magnetic field and treatment with enhancement solution; then, fluorescences were measured according to the number of europium ions dissociated. Results: The working concentrations ranged from 0.05 to 100 ng/mL, and the sensitivity was 0.5 μg/Kg in cereal. The intra–assay CVs of corn and wheat were 5.7% and 7.1%, respectively. The recovery rates obtained using cereal sample were 83.2%–120.0%. Conclusion: This study suggested that the Eu-chelate antibody-conjugated magnetic nanoparticles method was fast and sensitive in screening large quantities of samples, and could be used for detection of DON in cereal.